Global perspectives on mentoring : transforming contexts, communities, and cultures - Kochan, Frances K.; Pascarelli, Joseph T. (Perspectives in mentoring., 2003)
This volume examines mentoring from a global persepctive in an effort to discover the commonalities and differences, not only in diverse fields of practice, but also across a wide range of contextual settings. Each chapter contains an overview of the programme, problems encountered and solutions.